Pengaruh Latihan Push-Up Standar dan Clapping Push-Up terhadap Ketepatan Smash Siswa Ekstrakurikuler Bolavoli - Payoga, Teguh Yudistiara; Nurina, Titis; Septiadi, Firman (utile: Jurnal Kependidikan, 2019)
The problem in this study is the lack of accuracy of smash in volleyball games, this study aims to determine the results of accuracy smash after being given treatment in the form of push ups standard and clapping push up against volleyball extracurricular students at MTs Negeri 1 Sukabumi. The design in this study was experimental, data collection using tests, instruments used ability tests smash, namely tests to determine students' abilities, data analysis techniques using t-test (t test), normality and homogeneity test. The results of the t-test hypothesis testing 1) There is the effect of exercises push-up standard with tcount (4.38)> ttable (1.73) the significance level Î± 0.05. 2) There is the effect of aexercise clapping push up with tcount (6.18)> ttable (1.73) a significant level Î± 0.05. The conclusions of this study are: 1) There is the influence ofexercises push-up standard on the accuracy of smash volleyball. 2) There is the influence of the practice of clapping push ups on the accuracy of smash volleyball. 3)exercises clapping push up have more influence on the accuracy of the smash volleyball extracurricular students.